DETERMINING THE RESULTS OF RADIOISOTOPE PRODUCTIN DECY-13 CYCLOTRON FACILITY - - Silakhudin (Jurnal Penelitian Saintek, 2016)
This study was aimed at determining the results of radioisotope product in particular radioisotope of ﬂ uorine-18 at 13 MeV proton cyclotron facility. The calculation used a formulae of thick target yield on the nuclear reaction of 18 O(p,n) 18 F. This calculation is intended to ensure that the formulae and parameters used quite feasible for commissioning DECY-13 cyclotron. The calculation result has been compared with the radioisotope results of the cyclotrons in Dharmais and MRCCC Jakarta hospitals as well as the standards of the IAEA. The difference of results of calculation with comparison data is not more than 5%, which means that the calculation formulae is quite feasible for cyclotron commissioning. The calculation of ﬂ uorine-18 product using the formulae is 1223 mCi at 30 uA proton beam current of cyclotron operation and 40 minutes of irradiation.